Comparison of Burnout Syndrome Frequency between General Family Physicians and Other General Physicians, in Mazandaran Province, Iran, in 2018 - Zahra Rahnama; Mahshid Ahmadi; Alireza Khalilian; Maryam Sefidgarnia Amiri (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: Job burnout is a kind of psychological distress that results from various occupational factors and leads to the deterioration of job performance. This condition is usually characterized by weakness, disappointment, and nonachievement of career goals. Regarding this, the present study aimed to compare the frequency of burnout syndrome between general family and non-family physicians in Mazandaran province, Iran, in 2018. Methods: This cross-sectional study was conducted on 153 urban family physicians, 158 rural family physicians, and 295 non-family physicians (i.e., a total of 606 cases) selected using simple random sampling technique. In this study, Maslach Burnout Questionnaire was used, as the main tool for measuring the three dimensions of emotional exhaustion, depersonalization, and personal empowerment. Study participants included two groups of family general practitioners with more than two years of experience working in all shifts as a family physician, as well as non-family general practitioners working in health centers and offices affiliated to mazandaran university of medical sciences. General practitioners working in the hospital and staffing plan were excluded from the study. One-way ANOVA was used to compare the mean values and the mean differences of burnout dimensions at two levels of urban and rural family physicians and those outside the family physician plan. Results: Emotional exhaustion score in the non-family physicians was 14.6±10.31, while this score was obtained as 19.73±12.57 and 20.39±12.17 in the urban and rural family physicians, respectively, showing a statistically significant difference (P<0.0001). In this regard, family physicians (especially rural family physicians) had the highest occupational burnout in this dimension. However, regarding the other two dimensions, the difference between the family and non-family physicians was not statistically significant. Generally, emotional exhaustion had the highest prevalence (20.3 %), followed by depersonalization (29.4%) and personal accomplishment (24.1%). In addition, more than half of the subjects showed a high level of burnout at least in one of the three dimensions of this construct. Conclusion: As the findings indicated, occupational burnout was more common in family physicians, especially in rural area family physicians, which can be due to working in remote places with more duties, fewer facilities, and more difficult environmental conditions. Many demographic and environmental factors account for the incidence of burnout. Therefore, it is required to perform further studies and develop plans targeted toward reducing occupational burnout, especially in family physicians, since resolving this situation can improve the quality of patient care services.